Role of solar power in shifting the Turkish electricity sector towards sustainability - KURŞUN, BERRİN (My University, 2022)
Abstract This work covers a three-stage evaluation: cradle-to-grave life-cycle assessment (LCA) of polycrystalline silicon (pc-Si) and monocrystalline silicon (mc-Si) solar photovoltaics (PVs) as on-grid utility-scale energy options; environmental-impact distribution of pc-Si and mc-Si combinations under local conditions in Turkey; and assessment of the role of solar power in improving the environmental performance of the Turkish electricity mix. In LCA, mc-Si panels are found to have 4.47–9.16% higher environmental impacts than pc-Si panels in absolute terms. However, the higher efficiency and slower degradation rate of mc-Si panels make them have lower impacts on a kWh electricity basis. For the solar PV combination, the global-warming potential (GWP) and human-toxicity potential (HTP) results are found to be significantly lower than that of home-scale pc-Si systems (27.1–34.4 g versus 33.7–59.9 g CO2 equivalent (eq)/kWh 30.6–38.9 g versus 65.9–117 g 1–4 dichlorobenzene (g 1–4 DB) eq/kWh) operating in Turkey due to the higher capacity and efficiency of the utility-scale system. This result reveals the advantage of utilizing solar power as a centralized energy option for the country. All of the eight impacts that we evaluated reduce increasingly with increasing solar percentage in the electricity mix. The general tendency is that each percentage increase in solar electricity in the mix reduces each impact by ~1.0%. With a conservative assumption, if the solar power ratio in the mix increases to 15% by 2030, a GWP reduction of 31.3 million tons can be achieved. This corresponds to 12.7% of the greenhouse-gas mitigation commitment (246 million tons CO2 eq) made by Turkey under the United Nations Framework Convention on Climate Change. With the Turkish electricity sector being dominated by imported coal and natural gas, the obtained results reveal the potential of solar power in improving the environmental performance of the electricity mix in Turkey.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG); solar PV life-cycle assessment; Turkish electricity-mix life-cycle impacts; environmental performance improvement with solar energy; LIFE-CYCLE ASSESSMENT; ENVIRONMENTAL IMPACTS; ENERGY; GENERATION; SYSTEMS; TURKEY; solar PV life-cycle assessment; Turkish electricity-mix life-cycle impacts; environmental performance improvement with solar energy